Electrochemical behavior of gold-silver alloy nanoparticles - Plowman, B; Sidhureddy, B; Sokolov, S; Young, N; Chen, A; Compton, R (Wiley, 2016)
We report the voltammetry of alloy nanoparticles via the cyclic voltammetry of gold-silver alloy nanoparticles. Through careful comparison with the response of pure gold nanoparticles, pure silver nanoparticles and their mixture the contrasting electrochemical behavior of the alloy nanoparticles is established, providing insights into the electrochemical stability of gold-silver alloy nanoparticles in chloride-containing media.